Numerical simulation and experimental investigation of remelting processes. - Jardy, А. (Автоматическая сварка, 2013)
The numerical simulation of remelting processes enables us to link the local solidification conditions to the operating parameters. Here, we discuss some recent studies aiming to develop specific aspects, e.g. the alternating current distribution during ESR of steels and superalloys, the ensemble arc motion in a VAR furnace and the influence of electromagnetic stirring on the macrosegregation in remelted ingots